The shift in the translation of Japanese compound sentences into Indonesian in the novel Tokyo Tower by Lily Franky - Laily Fitriani; Nuria Haristiani; Dedi Sutedi (Chi'e: Journal of Japanese Learning and Teaching, 2022)
Indonesian sentence structure with a subject-verb-object pattern differs from Japanese sentence structure with a subject-object-verb pattern. This significant difference in grammatical structure often creates difficulties in translating Japanese into Indonesian, especially in translating written texts with long or compound sentences. This article tries to analyze the translation of Japanese compound sentences into Indonesian from the aspect of translation shift. This study will explain the shift in translating Japanese compound sentences into Indonesian. This research is a qualitative descriptive study. The data sources of this research were taken from the Japanese novel Tokyo Tower by Lily Franky and the Indonesian translation of the novel with the same title. The result is 270 compound sentences as finding data. This study analyzes compound sentence data using translation shift theory according to Catford (1965), which is classified into six types: a level shift from lexical level to grammatical level, a level shift from grammatical level to lexical level, a structure shift, a class shift, a unit shift, and intrasystem shifts. The shift in structure is a definite thing because of the differences in the sentence structure between Japanese and Indonesian, especially in the translation of compound sentences. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Translation StudiesJapanese CompoundJapanese Translation Shifting